Hubungan Antara Ketaatan Beribadah (Indikator PAI) dengan Pengambilan Keputusan Investasi Syariah Masyarakat Perkotaan - Indra Nur Ashari (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2026)
This study aims to examine the relationship between religious compliance measured through official Islamic Religious Education (PAI) indicators and sharia investment decision-making among urban communities in Bandar Lampung. The research uses a quantitative associative method with a sample of 384 Muslim residents aged 18-60 years. Data were collected using questionnaires and analyzed with correlation and simple linear regression tests. The results show a strong, positive, and significant relationship between religious compliance and sharia investment decisions (r = 0.724; p < 0.05), with sharia muamalah understanding being the most influential dimension. Religious compliance contributes 52.4% to investment decision variations, while the remaining portion is influenced by other factors. This study confirms that religious values serve as a core moral compass in economic choices, and fills the research gap in Southern Sumatra regarding this specific topic.